Information security of management of the system of economic security of the enterprise and its improvement - Machak, Tatiana; Мачак, Тетяна Олександрівна (Дніпровський державний аграрно-економічний університет, 2024)
In the modern conditions of information transformation, the need to ensure the protection of information resources of the enterprise appears quite acutely. Of great importance in the management system of economic security of an agrarian enterprise is information support, which is a set of information, accounting, regulatory sources and methods of assessment and analysis of the level of economic security of the enterprise. The issue of protection of information sources during the processing, storage and exchange of accounting and management data and the development of a plan to minimize the impact of possible threats and dangers of various origins during the activity of agricultural enterprises require constant attention. Since threats to the information security of the enterprise can arise under the influence of both internal and external factors, ensuring the appropriate level of information protection is important for the decision-making process of the management and directly affects the state of economic security of the enterprise В сучасних умовах інформаційної трансформації досить гостро постає необхідність забезпечення захисту інформаційних ресурсів підприємства. Важливе значення в системі управління економічною безпекою аграрного підприємства має інформаційне забезпечення, яке являє собою сукупність інформаційних, облікових, нормативних джерел і методів оцінки та аналізу рівня економічної безпеки підприємства. Постійної уваги потребують питання захисту джерел інформації під час обробки, зберігання та обміну обліково-управлінськими даними та розроблення плану мінімізації впливу можливих загроз і небезпек різного походження під час діяльності сільськогосподарських підприємств. Оскільки загрози інформаційній безпеці підприємства можуть виникати під впливом як внутрішніх, так і зовнішніх факторів, забезпечення належного рівня захисту інформації є важливим для процесу прийняття рішень керівництвом і безпосередньо впливає на стан економічної безпеки підприємства.
Інформаційна безпека управління системою економічної безпеки підприємства та її вдосконалення
Keywords: Economic security; економічна безпека; security management; управління безпекою; information security; інформаційна безпека; ensuring information security; забезпечення інформаційної безпеки; information protection; захист інформації